Influence of the abutment height and connection timing in early peri‐implant marginal bone changes: A prospective randomized clinical trial. Issue 9 (26th September 2018) - Borges, Tiago; Leitão, Bruno; Pereira, Miguel; Carvalho, Ágata; Galindo‐Moreno, Pablo
Abstract: Aim: The aim of this study was to compare the influence of the abutment height and insertion timing on early marginal bone loss (MBL) in posterior mandibular partial implant‐supported restorations. Material and methods: The study was planned as a prospective, randomized, controlled parallel group including subjects in need of at least two implants for the restoration of an edentulous posterior mandibular area. The patients were allocated into Groups A (implants immediately connected to 2‐mm height abutments), B (immediately connected 1‐mm height abutments), and C (2‐mm abutments were inserted in a second‐stage surgery). Each subject was placed in a 1‐year follow‐up program, including examination assessment of various soft tissue and bone‐level parameters. Results: A total of thirty‐three patients, including sixty‐eight implants, were enrolled in this study. One implant was lost on group C after the first month of healing. A mean MBL change of 0.719 ± 0.361, 0.651 ± 0.379, and 0.754 ± 0.672 mm was computed for groups A, B, and C, respectively, with no significant differences found. The early MBL at T1 was an independent predictor variable for the marginal bone alterations that were assessed at T3 ( p < 0.001). Conclusion: The first‐month MBL variation is a predictor factor of the bone alterations that might occur after 1 year of treatment. The early connection of final prosthetic abutments with distinct heights does not seem to reduce the 1‐year MBL rate when compared with traditional treatment protocols.